2017
DOI: 10.1007/s00403-017-1783-7
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric mycosis fungoides: a study of the human leukocyte antigen system among Israeli Jewish patients

Abstract: Pediatric mycosis fungoides (MF) is a rare disease characterized by over-representation of atypical clinical variants, with a different prognosis from adult MF. Several human leukocyte antigen (HLA) alleles have been associated with MF in certain adult populations, including Israeli Jews. However, HLA data on pediatric MF as a group are lacking. To evaluate the possible association of the HLA system with pediatric MF, 59 Israeli Jewish patients diagnosed with MF at age ≤ 18 years underwent high- and intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…16 In a very recent case-control study evaluating the association between paediatric MF and HLA system, HLA class I and class II allele frequencies did not differ. 20 Our study was limited by the small sample size. Larger sample trials with subgroup analyses according to family history, ethnicity and clinicopathologic variant are needed.…”
Section: Discussionmentioning
confidence: 94%
“…16 In a very recent case-control study evaluating the association between paediatric MF and HLA system, HLA class I and class II allele frequencies did not differ. 20 Our study was limited by the small sample size. Larger sample trials with subgroup analyses according to family history, ethnicity and clinicopathologic variant are needed.…”
Section: Discussionmentioning
confidence: 94%
“…Most of the studies report hypopigmented MF as the predominant variant accounting for almost 55-100% of the cases. 11,15,20,[30][31][32][33] Other common variants reported are the classical MF, which may account for 15-40% of the cases, 4,9,10,34,35 folliculotropic variant (3-36%), 4,9,11,34 and poikilodermatous MF (5-26%). 16,36 There are few uncommon variants which have been reported in children including pityriasis lichenoides chronica-like (PLC) MF, unilesional MF, pigmented purpuric dermatosis-like MF, granulomatous MF, ichthyosiform MF, hyperpigmented and intraoral presentation, inflammatory linear verrucous epidermal nevus-like MF, and pagetoid reticulosis, which may at times be difficult to diagnose at the initial presentation.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…16,36 There are few uncommon variants which have been reported in children including pityriasis lichenoides chronica-like (PLC) MF, unilesional MF, pigmented purpuric dermatosis-like MF, granulomatous MF, ichthyosiform MF, hyperpigmented and intraoral presentation, inflammatory linear verrucous epidermal nevus-like MF, and pagetoid reticulosis, which may at times be difficult to diagnose at the initial presentation. 20,[37][38][39][40][41][42][43][44] Few rare cases of familial MF and MF post organ transplant have also been reported 21,45,46 (Table 1). Mycosis fungoides with largecell transformation in children is extremely rare and hence lacks a standardized therapeutic regimen.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][23][24][25][26][27][28][29] Pediatric MF may show the classic presentation of erythematous patches and plaques with lymphocyte epidermotropism, yet various atypical clinical variants have been reported, including hypopigmented, psoriasiform, granulomatous slack skin, follicular, poikilodermic and purpuric. 19,[21][22][23]29,30 The hypopigmented variant seems to be overrepresented in childhood MF, 19,22,24,25,[28][29][30][31][32] and this clinical subtype is more often associated with a cytotoxic phenotype with expression of CD8 and TIA-1 reflecting the adequate antitumor immune response, which explains the better prognosis of that variant. 31,33 The association of MF with PLC has already been noted in other studies 33,34 and has been reported in a ratio as high as four out of five patients.…”
Section: Cutis))mentioning
confidence: 99%